2011
DOI: 10.1111/j.1365-2427.2010.02551.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and physiological changes in Microcystis aeruginosa as a result of interactions with heterotrophic bacteria

Abstract: SUMMARY1. To reveal the role of aquatic heterotrophic bacteria in the process of development of Microcystis blooms in natural waters, we cocultured unicellular Microcystis aeruginosa with a natural Microcystis-associated heterotrophic bacterial community. 2. Unicellular M. aeruginosa at different initial cell densities aggregated into colonies in the presence of heterotrophic bacteria, while axenic Microcystis continued to grow as single cells. The specific growth rate, the chl a content, the maximum electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(91 citation statements)
references
References 68 publications
3
84
1
3
Order By: Relevance
“…A potential clue to colony formation in Trichodesmium, or at least a testable hypothesis, may come from recent research with the freshwater cyanobacteria, Microcystis spp., which showed that certain distinct "specialist bacteria" may trigger extracellular polysaccharide production and colony formation of otherwise single cells of Microcystis spp. (Shen et al, 2011).…”
Section: Trichodesmium Morphologymentioning
confidence: 99%
“…A potential clue to colony formation in Trichodesmium, or at least a testable hypothesis, may come from recent research with the freshwater cyanobacteria, Microcystis spp., which showed that certain distinct "specialist bacteria" may trigger extracellular polysaccharide production and colony formation of otherwise single cells of Microcystis spp. (Shen et al, 2011).…”
Section: Trichodesmium Morphologymentioning
confidence: 99%
“…To date, research efforts have broadly identified nutrient inputs and temperature as contributing factors in the development of such blooms, but little focus, due primarily to methodological limitations, has been allocated to the study of the cellular physiology and metabolism of the entire bloom community. Not only do bloom-forming organisms such as Microcystis aeruginosa live in competition with other phytoplankton species, they also live in concert with heterotrophic bacteria, which can attach to the mucilaginous matrix produced by M. aeruginosa colonies (15,16). There is a dearth of information concerning the functional role that co-occurring bacteria may play in bloom dynamics, although recent studies suggest that heterotrophs may play an important role in the metabolism of some nutrients (17,18).…”
mentioning
confidence: 97%
“…Free-living bacteria may not influence aggregation whereas bacteria attaching to these microalgal cells may increase aggregate formation (Gardes et al, 2011). Shen et al (2011) used PCR-DGGE to reveal the role of aquatic heterotrophic bacteria in the process of development of Microcystis aeruginosa blooms in natural waters. Their results suggested that Porphyrobacter, Flavobacteriaceae and one uncultured bacterium could be specialist bacteria responsible for aggregation of M. aeruginosa.…”
Section: Harvesting Of Biofuel Producing Microalgaementioning
confidence: 99%